Efectos del termotratamiento sobre las propiedades físicas, químicas y mecánicas en la madera de Tectona grandis y Gmelina arborea proveniente de plantaciones forestales. - Méndez-Mejías, Luis Diego (Instituto Tecnológico de Costa Rica., 2016)
In recent years, new techniques and processes have emerged, such as heat treatment to modify and improve the properties of wood. This study evaluated the effect of thermo-treatment on physical properties (density, shrinking, mass loss, moisture absorption) color measured by the CieLab system, durability by accelerated testing of natural rot resistance, mechanics such as MOR and MOE in flexion, stress adhesion and chemicals by FTIR in wood of Tectona grandis and Gmelina arborea. Sapwood and heartwood samples, sawn under radial and tangential cutting patterns for T. grandis species and wood samples sawn under the radial and tangential cutting patterns for G. arborea were exposed to four temperature levels (205, 210, 215 and 220 ° C) and (185, 190, 195 and 200 ° C) respectively, plus control samples (without thermo-treatment) for each species. Results showed that density varied from 0.61 g cm-3 to 049 g cm-3 and from 0.43 g cm-3 to 0.47 g cm-3 fot T. grandis and G. arborea respectively, with a declining trend as temperature of the thermo-treatment increases in both species.
Proyecto de Graduación (Maestría en Ciencias Forestales) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2016.
Keywords: Estabilidad dimensional; Madera; Tratamiento térmico; Color de la madera; Densidad de la madera